Diseño y evaluación económica comparativa del sistema de agua potable en la comunidad de nuevo Arica de Cachiyacu utilizando energía solar y energía térmica en el año 2010 - Cunia Pérez, Gabriela Claudia (2012)
Based on the need for basic services such as drinking water in remote communities where usually there is the power of a network service to feed a water pumping system, seeking other sources of energy supply. Of engineering this thesis has been developed at the community level Kechwa new Arica de Cachiyacu, located in the District of San José de Sisa, province of El Dorado, in the Department of San Martin in the year 2010. This research has been done drinking water system design, where it has been considered the use of a submersible pump for pumping the water. The community of Nuevo Arica account with electricity to power the pump, is not therefore is proposing two types energy: the energf solar and thermal energy; then pumping with every type of energy system has been designed. The comparison is performed using the source to generate energy, with l...